Stability and toxicity of Clostridium perfringens type D epsilon prototoxin treated by iodine Estabilidade e toxicidade da protoxina epsilon de Clostridium perfringens tipo D - P.H. Rocha; R.A. Assis; F.C.F. Lobato; V.N. Cardoso; L.G.D. Heneine (Arquivo Brasileiro de Medicina Veterinária e Zootecnia, 2008)
Purified epsilon prototoxin of Clostridium perfringens type D was produced, purified, and detoxified by the stoiechiometric method of non-radioactive iodine incorporation. Different degrees of iodination were perfomed and the toxicity of the derivatives were analysed by in vivo studies. Toxicity decreased inversely to the iodine incorporation. Eletrophoretic analysis showed different levels of stability of samples kept under different temperatures 4ºC, - 20ºC, and -80 ºC. The iodinated prototoxins were stocked for a period of four months. A prototoxina epsílon de Clostridium perfringens tipo D foi produzida, purificada e destoxificada por estoiquiometria. Diferentes quantidades de iodo foram incorporadas à estrutura protéica da prototoxina e a toxicidade dos derivados foi analisada em estudos in vivo. Verificou-se que a toxicidade diminuiu à medida que os átomos de iodo foram incorporados à prototoxina. A análise eletroforética demonstrou a estabilidade das amostras quando armazenadas a 4ºC, -20ºC e -80ºC. A prototoxina iodada foi estocada por um período de quatro meses.